Analysis of Mathematical Methods and Models which are Used for the Process of Management of Commodity Stocks in Retail Trade - Ivchenkova, H.Y.; Lyakh, A.O. (Економічний вісник Донбасу, 2015)
The article discusses the concept of inventory, role in a company's activities. The authors made a comparative analysis of existing mate-automatic methods, followed by the formation of the table. The scheme of classification of mathematical models for the management of inventory. У статті розглянуто поняття товарних запасів, роль у підприємницької діяльності. Автори зробили порівняльний аналіз існуючих математичних методів з наступним формуванням таблиці. Складена схема класифікації математичних моделей з управління товарних запасів. В статье рассмотрены понятие товарных запасов, роль в предпринимательской деятельности. Авторы сделали сравнительный анализ существующих математических методов с последующим формированием таблицы. Составлена схема классификации математических моделей по управлению товарных запасов.